2020
DOI: 10.1136/heartjnl-2020-317009
|View full text |Cite
|
Sign up to set email alerts
|

Chronobiological patterns of acute aortic dissection in central China

Abstract: BackgroundAcute aortic dissection (AAD) is a life-threatening emergency with poor clinical outcomes. Understanding the chronological patterns of AAD onset would be helpful for identifying the triggers of AAD and preventing this catastrophic event.MethodsWe collected data from 2048 patients diagnosed with AAD at Tongji Hospital (Wuhan, China) from 2011 to 2018. The χ2 test was used to determine whether a specific period had significantly different seasonal/weekly distributions from other periods. Fourier models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…In 1999, Manfredini et al [ 62 ] studied monthly data from 85 AAD patients and demonstrated a circannual pattern with a peak of maximal occurrence in January/winter/cold season. Since then, increasing numbers of large-cohort studies confirmed these findings of AAD onset patterns from different locations of the northern hemisphere [ 58 , 59 , 60 , 63 , 64 , 65 ]. Despite the lack of AAD data from the southern hemisphere, two recent studies revealed similar seasonal pattern in cervical artery dissection in Australia and the latest study showed consistent increased risk of cervical artery dissection in cooler months [ 66 , 67 ].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In 1999, Manfredini et al [ 62 ] studied monthly data from 85 AAD patients and demonstrated a circannual pattern with a peak of maximal occurrence in January/winter/cold season. Since then, increasing numbers of large-cohort studies confirmed these findings of AAD onset patterns from different locations of the northern hemisphere [ 58 , 59 , 60 , 63 , 64 , 65 ]. Despite the lack of AAD data from the southern hemisphere, two recent studies revealed similar seasonal pattern in cervical artery dissection in Australia and the latest study showed consistent increased risk of cervical artery dissection in cooler months [ 66 , 67 ].…”
Section: Introductionmentioning
confidence: 88%
“…A few early studies identified a relative higher AAD risk on Monday than other days of a week [ 59 , 60 , 68 ], but this pattern was not confirmed in more recent studies [ 65 , 69 , 70 ]. However, there is a significantly higher in-hospital mortality rate in patients admitted for AAD or rupture on weekends compared with weekdays [ 70 , 71 ].…”
Section: Introductionmentioning
confidence: 97%
“…A group of studies examining the temporal distribution of certain diseases that are prone to circadian and septadian rhythmicity distinctly point to an increased risk of MI, IS, sudden deaths, acute aortic dissections (AAD), and cardiac arrests on Mondays [36][37][38][39][40][41] . Challenging these established conclusions, recent data looking at sudden cardiac deaths and AAD suggest however that such temporal distribution either fades or become no longer significant, as psychosocial stressors-prominent triggers of cardiovascular accidents-tend to be more evenly distributed across the entire week 42,43 . Significant associations with the first day of the week have also been reported for suicide, road traffic and workplace accidents [44][45][46][47][48][49] .…”
Section: Dst and Mortalitymentioning
confidence: 97%
“…Previous studies have described AAD as one of the most catastrophic, life-threatening cardiovascular diseases with a typical chronobiological pattern, associated with extremely poor outcomes and a high risk of readmission (20)(21)(22)(23). AAD was described as a high incidence during the cold period, with a peak in January (22), suggesting a potential connection between climate characteristics and the onset of AAD.…”
Section: Discussionmentioning
confidence: 99%